2014
DOI: 10.1073/pnas.1323098111
|View full text |Cite
|
Sign up to set email alerts
|

Feedback regulation mediated by Bcl-2 and DARPP-32 regulates inositol 1,4,5-trisphosphate receptor phosphorylation and promotes cell survival

Abstract: Significance The B-cell lymphoma-2 (Bcl-2) protein binds to the inositol 1,4,5-trisphosphate receptor (InsP 3 R), a ubiquitous intracellular Ca 2+ channel, thereby promoting cell survival by preventing excessive Ca 2+ elevation. We report here that this mechanism involves Bcl-2 interaction with the Ca 2+ -activated protein phosphatase calcineurin (CaN) and dopamine- and cAMP-regulated phosphop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 37 publications
1
46
0
1
Order By: Relevance
“…In addition to pro-apoptotic Bcl2 family members such as Bax, BH4 domains can also interact with inositol 1,4,5-trisphosphate receptors (IP 3 Rs) such as IP 3 R1 (Chang et al, 2014; Distelhorst and Bootman, 2011; Greenberg et al, 2014; Oakes et al, 2005; Rong et al, 2009). Notably, IP 3 R1 has been implicated in injury-induced axon degeneration (Villegas et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pro-apoptotic Bcl2 family members such as Bax, BH4 domains can also interact with inositol 1,4,5-trisphosphate receptors (IP 3 Rs) such as IP 3 R1 (Chang et al, 2014; Distelhorst and Bootman, 2011; Greenberg et al, 2014; Oakes et al, 2005; Rong et al, 2009). Notably, IP 3 R1 has been implicated in injury-induced axon degeneration (Villegas et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear if Bcl-2 inhibits Ca 2+ signaling directly by binding to the channel or if it acts indirectly, as a hub in a protein complex that influences channel phosphorylation (38). Conversely, we demonstrated that Bcl-x L , Bcl-2, and Mcl-1 bind to the carboxyl (C)-terminus of all three InsP 3 R isoforms, and showed that these interactions activated single InsP 3 R channels and promoted InsP 3 R-mediated Ca 2+ release and apoptosis resistance (27,31,32).…”
Section: Significancementioning
confidence: 99%
“…[12]. In T-lymphocytes however Bcl-2 can dock both DARPP-32 and calcineurin to the IP3R, whereby the PKA-mediated phosphorylation of the latter is antagonized, leading to decreased IP3R-mediated Ca 2+ release [13]. Very recently, in an siRNA screen for the identification of ER Ca 2+ -leak channels, IP3R1 channels emerged as one of the most prominent Ca 2+ -transport systems implicated in ER Ca 2+ leak [14].…”
Section: Introductionmentioning
confidence: 99%